Application of the Socratic Method-Based e-Learning Media in Linear Algebra Lectures - Dona Fitriawan; Nurfadilah Siregar; Endar Sulistyowati (Jurnal Pendidikan MIPA, 2022)
This study aims to determine the application of the Socratic method in the LMS model platform at Tanjungpura University e-learning. The use of e-learning from UNTAN has been applied by researchers for 4 semesters and the Socratic method is the reference for research in this semester. The Socratic method is a learning method with a discussion process led by educators to make students think about the truth of the validity of their reasoning or to reach a correct conclusion. The whole conversation is a constructive conversation and uses Socratic questions in building learning. The data in this study were given before and after the Socratic method was applied. The quantitative method in a comparative form is the type of this research. The research population is second semester students who take elementary linear algebra courses which are divided into 4 classes, namely class IIA1, II A2, IIA3, and B. The research sample was taken with consideration because the researcher was in charge of the class, namely class IIA2. The data obtained were analyzed descriptively by using the t test. The results of data analysis showed that there was a significant increase in learning outcomes after the implementation of the Socratic method in learning in the Tanjungpura University model e learning platform.Keywords: e-learning moodle, learning outcomes, socratic method.DOI: http://dx.doi.org/10.23960/jpmipa/v23i3.pp1173-1180